Analysis of Demak Regency Regional Regulation Number 11 of 2018 Concerning the Implementation of Entertainment Businesses in Demak Regency - Ahmad Turmudi; Vicki Dwi Purnomo; Benedictus Hestu Cipto Handoyo; Syukron Abdul Kadir (PT FORMOSA CENDEKIA GLOBAL, 2023)
Whereas the entertainment business is a strategic business that supports regional tourism development, increases investment and regional income, as well as creates jobs and increases people's income; that entertainment businesses must pay attention to public order and public safety, and not conflict with religious norms, laws, customs and noble values that are upheld in society; Demak Regency. Whereas in this study the emphasis is on the analysis of the regional regulations which describe the formulation of the problem, the focus of the analysis of the regional regulations, the results of the discussion of the regional regulations which include: Evaluation of the regional regulations on the Implementation of Entertainment Business which includes the Urgency of evaluating the Regional Regulations of Demak Regency as well as Analysis, Evaluation of regional regulations and then ends with conclusions, suggestions -suggestions and bibliography.